DEVELOPING RICH LANGUAGE LEARNING ENVIRONMENT TO SUPPORT SIXTH GRADE STUDENT’S ENGLISH LITERACY SKILLS IN PRIMARY SCHOOLS IN BALI PROVINCE - Nurpratiwi, Ni Made; Artini, Luh Putu; Marhaeni, A.A.I.N. (Jurnal Pendidikan Bahasa Inggris Indonesia, 2013)
Abstract This study was a research and development (R&D) which aimed at finding out the literacy coverage of English teaching; investigating what materials need to be developed to help students progress with their literacy skills in English; investigating the quality of the developed material; and finding the effect of material developed upon students? English literacy skills. The instruments used to collect the data in this study were checklist, scoring rubric, observation sheet, questionnaire and test. The material develop in this study was based on criteria of good material proposed by Tomlinson. The result of the study shown that the limited time in studying English at school resulted in limited chance to experience with literacy activities. There are three topics need to be inserted in this study, those are: transportation, occupation and parts of house. The new materials were created by using Multiple Literacy Experiences proposed by Winch (2006) and the criteria of good material proposed by Tomlinson. The RLLE material had high validity and practically where the value of validity was 4.37 (Good) and for practically could be categorized into Excellent. It can be concluded that RLLE material was proven to be effective to support the sixth grade students? literacy skills. Key Words: English literacy, rich language learning environment, material development.